The role of low educational attainment on the pathway from adolescent internalizing and externalizing problems to early adult labour market disconnection in the Dutch TRAILS cohort - Anita Minh; Christopher B. McLeod; Sijmen A. Reijneveld; Karin Veldman; Sander K.R. van Zon; Ute Bültmann (Elsevier, 2023)
Mental health challenges in adolescence may affect labour market transitions in young adulthood. Policies addressing early labour market disconnection largely focus on early school-leaving and educational attainment; however, the role of low educational attainment on the path from adolescent mental health to labour market disconnection is unclear. Using the TRacking Adolescents' Individual Lives Survey from the Netherlands (n = 1,197), we examined the extent to which achieving a basic educational qualification (by age 22) in the contemporary Dutch education system, mediates the effect of adolescent mental health (age 11-19) on early adult labour market disconnection, defined as 'not in education, employment, or training' (NEET, age 26). We estimated the total effect, the natural direct and indirect effects, and the controlled direct effects of internalizing and externalizing symptoms on NEET by gender. Among young men, clinical levels of adolescent externalizing symptoms were associated with a 0.093 higher probability of NEET compared with no symptoms (95% confidence interval, CI: 0.001, 0.440). The indirect effect through educational attainment accounted for 15.1% of the total effect. No evidence of mediation was observed for the relationship between externalizing symptoms and NEET in young women. No evidence of mediation was observed for the relationship between adolescent internalizing symptoms and NEET in either gender. The findings imply that adolescent externalizing symptoms disrupts the achievement of a basic educational qualification, leading to a higher probability of NEET in young men. This mechanism may play a smaller role in the risk of NEET associated with internalizing symptoms and in young women.